Microstructure characteristic of aluminium 6061 semi-solid feedstock billet produced with direct thermal method - Muhammad Faez, Mohamad Tajudin; Asnul Hadi, Ahmad; Juliawati, Alias; Nasrul Azuan, Alang; Naher, Sumsun (Penerbit Akademia Baru, 2023)
Semisolid metal processing is a promising technique to overcome the imperfections of the components produced by the traditional casting process. As a semi-solid metal processing technology, direct thermal method is capable of producing a feedstock billet with a spherical microstructure which is ideal for thixoforming. In this experiment, molten aluminium 6061 was solidified in a copper mould at temperatures between 660 °C and 680 °C. The melt was retained in the copper mould for 20 seconds, 40 seconds, and 60 seconds. The molten alloy in the mould was solidified in room-temperature water after the required holding time. The microstructure development of the feedstock billets was evaluated after the feedstock billets were removed from the mould. The results show that sample (S660-20), which had a pouring temperature of 660 °C and a holding time of 20 s, has the smallest grain size with an average of 2507.87µ m2. It was discovered that the ferret's diameter, aspect ratio and circularity were found to be 69.4 µm, 1.34 and 0.75 respectively. Clearly, the microstructure of S660-20 was more refined and spherical. The rapid cooling of the molten metal in the copper mould resulted in a more spherical grain structure. According to the findings, the microstructure was solely dependent on the heat convection between the molten alloy and the copper mould. The rapid cooling resulted in the production of finer and more spherical microstructure that was ideal for thixoforming operations.